The risks of RELN polymorphisms and its expression in the development of otosclerosis. - Saurabh Priyadarshi; Kirtal Hansdah; Neha Singh; Amal Bouzid; Chinmay Sundar Ray; Khirod Chandra Panda; Narayan Chandra Biswal; Ashim Desai; Jyotish Chandra Choudhury; Adel Tekari; Saber Masmoudi; Puppala Venkat Ramchander (PLoS ONE, 2022)
Otosclerosis (OTSC) is the primary form of conductive hearing loss characterized by abnormal bone remodelling within the otic capsule of the human middle ear. A genetic association of the RELN SNP rs3914132 with OTSC has been identified in European population. Previously, we showed a trend towards association of this polymorphism with OTSC and identified a rare variant rs74503667 in a familial case. Here, we genotyped these variants in an Indian cohort composed of 254 OTSC cases and 262 controls. We detected a significant association of rs3914132 with OTSC (OR = 0.569, 95%CI = 0.386-0.838, p = 0.0041). To confirm this finding, we completed a meta-analysis which revealed a significant association of the rs3914132 polymorphism with OTSC (Z = 6.707, p<0.0001) across different ethnic populations. Linkage analysis found the evidence of linkage at RELN locus (LOD score 2.1059) in the OTSC family which has shown the transmission of rare variant rs74503667 in the affected individuals. To understand the role of RELN and its receptors in the development of OTSC, we went further to perform a functional analysis of RELN/reelin. Here we detected a reduced RELN (p = 0.0068) and VLDLR (p = 0.0348) mRNA levels in the otosclerotic stapes tissues. Furthermore, a reduced reelin protein expression by immunohistochemistry was confirmed in the otosclerotic tissues. Electrophoretic mobility shift assays for rs3914132 and rs74503667 variants revealed an altered binding of transcription factors in the mutated sequences which indicates the regulatory role of these variations in the RELN gene regulation. Subsequently, we showed by scanning electron microscopy a change in stapes bone morphology of otosclerotic patients. In conclusion, this study evidenced that the rare variation rs74503667 and the common polymorphism rs3914132 in the RELN gene and its reduced expressions that were associated with OTSC.